A qualitative study to understand the facilitators of and barriers to retention in care to the national PMTCT Option B+ programme in Uganda. - Charity Kyomugisha-Nuwagaba; Rachel King; Rose Baryamutuma; Simon Muhumuza; Linda N Kisakye; William Bazeyo; Evelyn Akello (PLoS ONE)
Introduction Effective prevention of mother to child transmission (PMTCT) programmes require women and their infants to have access to a cascade of HIV care and treatment interventions. Retention in care reduces the risk of vertical transmission and opportunistic infections among mothers living with HIV. Uganda has made great strides in ensuring the success of the prevention of mother to child transmission program. Although an increasing number of people living with HIV (PLHIV) in Uganda are benefiting from the rapid scale-up of antiretroviral therapy (ART), retention in HIV care and treatment services remains a major concern. Identifying and understanding the reasons for dropping out of care among mothers enrolled in the Option B+ program among those who were retained and those who dropped out is key to inform policy and program practice. Methods We conducted a qualitative study to understand the facilitators of retention and reasons for loss to follow-up among HIV positive mothers in central Uganda who engaged in the Option B+ program. We conducted 29 focus group discussions (FGDs) with Village Health Teams (VHT) and 'Peer Mothers'. We performed 21 in depth interviews (IDI) with mothers who had been lost to follow up during the post-partum period, and 27 among those who remained in care. These were conducted in 18 districts in Central Uganda. Results Participants identified barriers and facilitators to retention in HIV care. Barriers included self-stigma and fear of disclosure, mental health challenges, community perceptions, poor health provider attitudes and structural challenges, lack of transportation and food, long waiting time at health facilities and client mobility. Both the clients retained and not retained in care discussed mental illness, feeling sick and competing priorities as barriers. Facilitators for retention in care included adequate community support systems, early initiation on ART, giving birth to HIV negative children and economic stability. These were noted as key enabling factors for retention. It was also highlighted that presence of friendly clinic staff members, scheduling reminders were important aspects of retention. Conclusion Findings highlighting barriers covering personal, interpersonal, structural and community suggest that developing client-centered models addressing social and community barriers and provide more holistic services is key to retaining mother-infant pairs in care. Emphasis on the use of community health workers and provision of financing, as well as institutionalization of quality improvement would provide alternatives for overcoming barriers to retention in care.